Política-poética dos dados: inquisições sobre novas formas do controle e do sensível - Almeida, Reno Beserra (2020)
Lev Manovich (2001) states that, in the contemporary society, permeated by the ubiquity of computational apparatuses, the database has become the main symbolic form from which we structure our experiences, giving rise to new modes of subjectivation, as well as new processes of regulation and management of bodies and minds. From an industry that makes continuous personal data monitoring its business model to global surveillance schemes, data, instrumentalized by different agents, becomes a privileged apparatus for ordering individuals, in more or less subtle ways, but with decisive consequences for different forms of lives. Departing from these questions, the present work proposes an investigation of the relationship between databases and exercises of control, unfolded in a theoretical and practical project. In a genealogical path that stems from modernity, reasoning the emergence of biopolitics and its regulation dispositives, to contemporary schemes of subjugation through information – society of control (DELEUZE) and surveillance capitalism (ZUBOFF) –, this work also highlights projects from different fields that brings to light such questions around data in a research that fosters a process of artistic creation. This process, by putting in motion the proposed investigation, articulates itself through a series of works and exercises that shed a light on different uses of information as a tool of subjection, proposing counterpoints and new sharings of the sensible experience through artistic practice.